Hazard proximities of childhood cancers in Great Britain from 1953-80. - Knox, E G (1997)
STUDY OBJECTIVES: Firstly, to examine relationships between the birth and death addresses of children dying from leukaemia and cancer in Great Britain, and the sites of potential environmental hazards; and secondly to measure relative case densities close to, and at increasing distances from, different hazard types. DESIGN: Home address postcodes (PCs) and their map coordinates were identified at birth and at death in children who died from leukaemia or cancer. Potentially hazardous industrial addresses and PCs were listed from business and other directories, and map coordinates obtained from the Central Postcode Directory or else located directly on Ordnance Survey (OS) maps. Railway lines and motorways were digitised from OS maps. Numbers of deaths (and births) at successive radial distances from these hazards were counted and compared with expected numbers. The latter were based on a count of all PCs at similar distances. Relative case density ratios at successive distances from the hazards were obtained from observed and expected numbers, aggregated over similar sites. This was repeated for different hazard types and results were tested for evidence of systematic centrifugal case density gradients. PARTICIPANTS AND SETTING: All 22,458 children dying from leukaemia or cancer aged 0-15 years, in England, Wales, and Scotland, between 1953 and 1980. MAIN RESULTS: Relative excesses of leukaemias and of solid cancers were found near the following: (1) oil refineries, major oil storage installations, railside oil distribution terminals and factories making bitumen products; (2) motor car factories, coach builders, and car body repairers; (3) major users of petroleum products including manufacturers of solvents, paint sprayers, fibreglass fabricators, paint and varnish makers, plastics and detergent manufacturers, and galvanisers; (4) users of kilns and furnaces including steelworks, power stations, galvanisers, cement makers, brickworks, crematoria and aluminium, zinc, and iron/steel foundries; (5) airfields, railways, motorways and harbours. The findings for leukaemias and for solid cancers were indistinguishable. The hazard proximities of birth addresses were stronger than for death addresses. For children who had moved house between birth and death, the proximity effect was limited to the birth addresses. CONCLUSIONS: Childhood cancers are geographically associated with two main types of industrial atmospheric effluent namely: (1) petroleum derived volatiles and (2) kiln and furnace smoke and gases, and effluents from internal combustion engines.